Analysis of 2013 curriculum problems so it is changed into a merdeka curriculum - Lestari, Nyoman Ayu Putri (JURNAL PENDIDIKAN DASAR NUSANTARA, 2023)
The purpose of this study was to analyze what problems occurred in the 2013 curriculum so that it was changed to the merdeka curriculum. This research is included in the qualitative descriptive research using the method narrative inquiry, namely the results of the research which is a detailed description of an event that we make the object of research, without exaggerating the information obtained regarding the analysis of the 2013 curriculum and the difficulties experienced so that it turns to the merdeka curriculum which is currently being discussed and being intensively implemented in schools elementary, starting from class I and class IV. From the results of the analysis, important findings were found, namely that there were 3 aspects of difficulties experienced by teachers in planning learning, carrying out learning and evaluating (learning assessment). So the Merdeka Curriculum was born which is a form of evaluation or refinement of the 2013 Curriculum, and is expected to be able to solve existing problems in the 2013 Curriculum. After going through a trial period of one year it can be said that the Merdeka Curriculum has provided a better picture than the previous Curriculum. Because, the Merdeka Curriculum found fewer problems and was able to solve problems in the 2013 Curriculum.